Manual switching between programs intended for specific real-life listening environments by adult cochlear implant users: do they use the intended program? - de Graaff, Feike; Huysmans, Elke; Merkus, Paul; Goverts, S. Theo; Kramer, Sophia E.; Smits, Cas (International Journal of Audiology, 2025)
Objective: The aim of the current study was to investigate the use of manually and automatically switching programs in everyday day life by adult cochlear implant (CI) users Design: Participants were fitted with an automatically switching sound processor setting and 2 manual programs for 3-week study periods. They received an extensive counselling session. Datalog information was used to analyse the listening environments identified by the sound processor, the program used and the number of program switches. Study samples: Fifteen adult Cochlear CI users. Average age 69 years (range: 57–85 years). Results: Speech recognition in noise was significantly better with the "noise" program than with the "quiet" program. On average, participants correctly classified 4 out of 5 listening environments in a laboratory setting. Participants switched, on average, less than once a day between the 2 manual programs and the sound processor was in the intended program 60% of the time. Conclusion: Adult CI users switch rarely between two manual programs and leave the sound processor often in a program not intended for the specific listening environment. A program that switches automatically between settings, therefore, seems to be a more appropriate option to optimise speech recognition performance in daily listening environments.